VALIDITAS MODUL DIGITAL INTERAKTIF BERBANTUAN HEYZINE FLIPBOOK BERPENDEKATAN DEEP LEARNING MATERI SIFAT CAHAYA KELAS V - Manurung, Widia Lestari; Chan, Faizal; Khoirunnisa, Khoirunnisa (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The development of an interactive digital module supported by Heyzine Flipbook and incorporating a deep learning approach aims to describe its validity level in IPAS instruction on the topic of light properties for fifth-grade elementary school students. This study employed a Research and Development (R&D) method using the ADDIE development model; however, the process was limited to the development stage because the study focused solely on evaluating product feasibility through expert validation, without conducting small-group or large-group trials. The analysis stage was carried out to identify learning needs, student characteristics, and problems encountered in IPAS learning on the topic of light properties. The design stage included outlining the module structure, preparing deep learning-based material, and designing an interactive module display using Heyzine Flipbook. The development stage involved developing the module based on the design and validating it by language, content, and media experts using validation sheets. The results showed that the module was categorized as very valid, with validity percentages of 96% for language aspects, 98% for content aspects, and 90% for media aspects. Therefore, the Heyzine Flipbook-assisted interactive digital module is highly feasible for use in IPAS learning on the topic of light properties in grade V elementary school. ABSTRAKPengembangan modul digital interaktif berbantuan Heyzine Flipbook dengan pendekatan deep learning ini bertujuan untuk mendeskripsikan tingkat validitasnya pada pembelajaran IPAS materi sifat cahaya bagi siswa kelas V Sekolah Dasar. Metode yang digunakan adalah Research and Development (R&D) dengan model pengembangan ADDIE, namun prosesnya dibatasi sampai tahap development karena fokus kajian hanya pada penilaian kelayakan produk melalui validasi ahli, tanpa uji coba kelompok kecil maupun kelompok besar. Tahap analysis dilakukan untuk mengidentifikasi kebutuhan pembelajaran, karakteristik siswa, serta permasalahan yang muncul dalam pembelajaran IPAS pada materi sifat cahaya. Tahap design meliputi perancangan struktur modul, penyusunan materi berbasis deep learning, dan desain tampilan interaktif menggunakan Heyzine Flipbook. Tahap development mencakup pengembangan modul sesuai rancangan dan validasi oleh ahli bahasa, ahli materi, serta ahli media menggunakan lembar validasi. Hasil validasi menunjukkan modul berada pada kategori sangat valid dengan persentase aspek bahasa 96%, aspek materi 98%, dan aspek media 90%. Dengan demikian, modul digital interaktif berbantuan Heyzine Flipbook dinyatakan sangat layak digunakan dalam pembelajaran IPAS materi sifat cahaya di kelas V Sekolah Dasar.